Emotional Intelligence, Mental Health, and Job Search Behaviors during Unemployment: The Mediating Role of Resilient Coping - Jorge Gómez-Hombrados; Natalio Extremera (Journal of Work and Organizational Psychology, 2023)

(untitled)
The scientific literature has shown interest in identifying psychological strengths that predict mental health and job search behaviors in the unemployed population. Emotional intelligence (EI) and resilience are key psychological resources, although there is a lack of understanding of underlying mechanisms involved during unemployment. In this study we aimed to examine whether resilient coping serves as a mediator between EI and depressive symptoms, happiness, and job search behaviors in unemployed. To prove whether resilient coping mediates this link, we recruited 401 unemployed through LinkedIn and asked them to complete self-report questionnaires. Correlational results showed significant relationships in the expected way. The results of the mediation analyses showed that resilient coping mediated the link between EI and job search behaviors, happiness, and depressive symptoms. The findings suggest that career counseling units should incorporate EI and resilience modules into their employability programs to promote the mental health and employability of the unemployed.